GLP-1 receptor agonists in the regulation of the brain–metabolism axis: implications for mental health - Michalik, Zuzanna; Kryś, Zuzanna; Kapelka, Klaudia; Bułka, Zofia; Chodor, Michał; Śliwiński, Kacper; Mirkowski, Karol (Journal of Education, Health and Sport, 2026)
Background: Glucagon-like peptide-1 receptor agonists (GLP-1RAs), widely used in the treatment of type 2 diabetes and obesity, have recently gained attention for their potential effects on the central nervous system and mental health, particularly within the metabolic–brain axis linking metabolic and neuropsychiatric processes. Aim: The aim of this study was to review the current evidence on the effects of GLP-1RAs on mental health, with particular focus on depression, cognitive function, substance use disorders, and psychiatric safety. Material and methods: A narrative review was conducted based on a targeted selection of review articles, including systematic reviews, meta-analyses, and comprehensive reviews identified in the PubMed/MEDLINE database; publications from the last five years were included using predefined inclusion and exclusion criteria, and the analysis focused on synthesizing the most clinically relevant findings. Results: GLP-1RAs may affect mental health through dopaminergic reward pathways, the HPA axis, and neuroinflammation. Meta-analyses show a small but significant reduction in depressive symptoms, and these drugs may also reduce addictive behaviors and improve eating patterns and cognitive function. Large-scale studies confirm a favorable psychiatric safety profile with no increased risk of adverse psychiatric events. Conclusions: GLP-1 receptor agonists show promise for mental health beyond their metabolic role, particularly for mood disorders and addiction. However, well-designed clinical studies are still needed to clarify the clinical relevance, durability, and practical applicability of these effects.